Kirchhoff plate modelling using finite element method - Nazihah Ismail, 1982-; Shaharuddin Salleh, supervisor; Fakulti Sains (2010)
Thesis (Sarjana Sains (Matematik)) - Universiti Teknologi Malaysia, 2010